A Systematic Review of Unfolding Teacher voices on Advantages and Difficulties in Implementing Merdeka Curriculum - Darussalam, Gilang Manik; Toyyibah, Toyyibah (Beyond Words, 2024)
The Merdeka Curriculum, introduced to replace the 2013 Curriculum, aims to improve educational quality in Indonesia. This systematic literature review explores teachers perspectives on the Merdeka Curriculum, focusing on the advantages and difficulties of its implementation. The findings show that while teachers hold a generally positive view of the curriculum, recognizing its potential to enhance learning outcomes, they face significant challenges in areas such as planning, executing lessons, and assessments. Teacher readiness is often deemed only sufficient, highlighting the need for further training to improve understanding and implementation skills. Despite these obstacles, the curriculum offers benefits, particularly in fostering student-centered learning and providing teachers with greater autonomy in designing educational activities. The study concludes that while the Merdeka Curriculum holds promise, its successful implementation requires addressing teacher preparedness and resource gaps.